Sistema para gestão da fila de espera em pronto-atendimento pediátrico usando aplicativo móvel - Souza, Glaucio Erlei de (2016)
Waiting queues in pediatric emergency unit are a constant problem in many hospitals in Brazil. The introduction of new technologies can contribute to the management of the queues. However, research about mobile applications to that address this problem was not identified. The present study developed two main activities that are related but independent. The first was the development of a cross-platform mobile application aimed at reducing the waiting queue in the pediatric emergency room of a major hospital in Curitiba. Using a pre-booking/check-in model, the application indicates time slots when the flux of patients is low in the emergency room. The model sought to achieve a balance between demand of treatment and hosting capacity that would help manage overcrowding and maintain the responsiveness in the service. The mobile application has three main features: to show the number of children that are waiting for care, to present the estimated waiting time for an appointment and a check-in system for the queue. During the 90-day evaluation of the prototype, 2,835 downloads and installations on mobile devices were carried out with 35,811 registered accesses. The second activity was the analysis of the effects of the check-in system use in the pediatric emergency department queue. The application proposes a time slot with fewer patients in the queue for the user, minimizing the risk of adverse events. 129 complete observations of patients who used the check-in function were obtained. The data related to three types of patients’ waiting times in queue were analyzed: the real waiting time in the room considering the check time in the application, the waiting time considering the scheduled time generated by the application, and the waiting time considering the actual arrival time at the hospital. To analyze the results, the three types of waiting times were compared using the statistical method of analysis time. In the 129 observations of patients who used the check-in, the analysis showed that on average, patients waited for care 19.24 minutes compared to the average time 127.8 minutes of waiting in the queue for patients who do not used the application. The proposed method of check-in reduced the waiting time for parents who used the application in comparison to other parents, indicating that it could be used to contribute to the management of the overcrowding in pediatric emergency unit.